Pengaruh Inklusi Keuangan Terhadap Stabilitas Perbankan Syariah di Indonesia Menggunakan Metode Generalized Least Square - Alwi, Alwi Muarif Sembiring; Laila, Nur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to find out whether financial inclusion has an effect on the stability of sharia banking in Indonesia using the Generalized Least Square (GLS) method. To measure the financial stability of Islamic banking, the inclusion variable contains MSMEs and Deposits, while the stability variable used is NPF. The research method used in this research is quantitative descriptive with the help of the Generalized Least Square (GLS) method which corrects problems in the classical assumption test, which is tested based on Eviews 12 with panel time series data. The research results show that the independent variable MSMEs has a significant effect on NPF. The independent variable Deposits has a significant effect on NPF. Reliability UI results using the F test for the MSME and Deposit variables together have an effect on NPF.